Spectroscopic models for laser-heated silicon and copper nanoparticles. (August 2017) - Daun, Kyle; Menser, Jan; Mansmann, Raphael; Moghaddam, Sina Talabi; Dreier, Thomas; Schulz, Christof
Abstract: Interpreting laser-induced incandescence (LII) measurements on aerosolized nanoparticles requires a spectroscopic model that relates the measured spectral incandescence to the temperature of the nanoparticles. We present spectroscopic models for molten silicon and copper nanoparticles, which are evaluated through extinction and incandescence measurements on nanoaerosols. Measurements on molten silicon nanoparticles are consistent with the Drude theory in the Rayleigh limit of Mie theory. The copper nanoparticles were initially assumed to coalesce into spheres, but the observed spectral incandescence does not show a surface plasmon polariton (SPP) peak in the vicinity of 600 nm expected of spheres. A simulation based on the discrete dipole approximation (DDA) suggests that this effect could be explained by the structure of the copper aggregates. Highlights: Laser-induced incandescence is a promising way to measure synthetic nanoparticles. Spectroscopic models are developed for silicon and copper nanoparticles. Absorption and emission by Si nanoparticles explained with Drude/Rayleigh theories. Cu nanoparticles do not show strong SPP peak at 600 nm expected from Mie theory. DDA is used to explain incandescence from Cu nanoparticles.